Effect of ballistic and power training on performance adaptations of élite table tennis players - Zaferanieh, A.; Haghighi, A. H.; Kakhak, S. A. H.; Ce, E.; Esposito, F. (Sport Sciences for Health, 2021)
The purpose of this study was to examine the effects of ballistic and power training on the skills, physical fitness and body composition adaptations of élite table tennis players. Thirty male table tennis players (age: 24 ± 7 years, stature: 175 ± 6 cm, body mass 74 ± 16 kg, percentage of fat mass (%FM) 12 ± 7%, mean ± SD), who were able to perform top spin strike properly, were randomly assigned to three groups: power training (PT), ballistic training (BT) and no training (Control, CON). PT and BT trained 3 times per week for 8 weeks. PT consisted of three sets for six different stations, 60-80% of one repetition maximum (1RM). BT consisted of three sets for five different throwing exercises. Pre- and post-intervention group comparisons were analyzed using a two-way ANOVA with repeated measurements of two factors (group × time). After training, significant interactions were observed in increasing muscle strength, muscle endurance, explosive power, anaerobic power, agility and grip strength regardless of the exercise methods (p < 0.05). Moreover, both training regimens were not effective in changing body composition, reaction time and skills (p > 0.05). In conclusion, the results of the present study suggest that physical fitness adaptations can be increased similarly after 8 weeks of power and ballistic training, in table tennis players. So coaches and elite table tennis players can use ballistic and power training to improve their performance without having to worry about the negative impact of their training on their skill and explosive power performance.